Kedudukan Pemilik Merek Terdaftar alam Sengketa Kekayaan Intelektual: Kajian Asas Priorin Tempora Nelior In Jure Berdasarkan Putusan NO. 1291 K/PDT.SUS-HKI/2023 - Dita Safitri Nurwidihantari; Dewi Sulistianingsih (Mahalini: Journal of Business Law, 2025)
Trademark protection is a crucial element within the Intellectual Property Rights (IPR) system, aimed at ensuring legal certainty while safeguarding the existence and reputation of a product or service. In Indonesia, trademark protection follows the first to file principle, whereby rights are granted to the party who first registers the trademark officially, regardless of prior usage. However, this system often gives rise to legal disputes, particularly when registration is carried out by unauthorized parties or with bad faith. This research specifically examines the Supreme Court of the Republic of Indonesia Decision Number 1291 K/Pdt.Sus-HKI/2023 in a dispute between Nitron Japan Co., Ltd., the original owner of the international trademark "NITRON" since 2008, and Harun Salim, who registered the same mark in Indonesia without permission or legal basis. Using normative legal research methods with statutory and conceptual approaches, the study aims to analyze how the principle of priorin tempora potior in jure is applied in trademark disputes involving bad-faith registrations. The findings show that although Harun Salim formally registered the trademark first in Indonesia, the Supreme Court acknowledged the presence of bad faith, making the registration subject to cancellation. Therefore, the principle of priority in time should not be interpreted solely from a formal perspective but also substantively, to protect rightful trademark owners who have built goodwill and reputation. This decision sets an important precedent for strengthening legal protection of registered trademarks amidst opportunistic registration practices.